Karakteristik Perkembangan Kognitif, Sosial dan Moral Masa Anak - Irma J Simanjuntak; Meliana Yulan Sari Sagala; Melvana Evriani Hutagalung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the characteristics of cognitive, social, and moral development of children aged 4–13 years and identify the challenges faced during their development process. Using a qualitative approach based on literature studies, data were obtained from various relevant academic sources. The results of the study indicate that cognitive development involves logical thinking and problem-solving skills, which are influenced by social and environmental interactions. Social development is influenced by parenting patterns, peer relationships, and media exposure, while moral development involves understanding the values ​​of right and wrong supported by the school and community environment. Children face various challenges, such as difficulties in emotional regulation, the negative impact of social media, and limited learning abilities. This study emphasizes the importance of collaboration between parents, educators, and the community to create an environment that supports children's holistic growth.